LEADERSHIP STYLES AND GENDER DEFERENCES AMONG NURSES (Vietnam Journal of Community Medicine, 2024)
Background: Competencies and leadership styles of managers play an essential role in everyorganization. It is evident that males and females tend to have different leadership styles. This studyaimed to describe the leadership styles and gender differences among nurses.Methods: In this cross-sectional descriptive study, participants were 260 nurses attending trainingcourses at Thai Nguyen University of Medicine and Pharmacy. The Leadership Style Questionnairewas used to assess the leadership styles of the nurses.Results: Nurses demonstrated the highest score on democratic, followed by autocratic, and then thelaissez-faire style, with average scores of 22.51 ± 2.59 (9.00 - 30.00), 18.77 ± 2.82 (7.00 – 29.00),and 18.34 ± 2.94 (9.00 - 27.00), respectively. There were no significant differences by gender in thedemocratic and laissez-faire leadership styles. However, males show a higher tendency to autocraticleadership styles than females (t=3.17; p=0.002).Conclusion: Democratic is the prominent leadership style among nurses. There is a difference in theauthoritarian style between males and females.
Keywords: Leadership styles, Nurse manager, Gender differences.